The Multichannel Analysis of Surface Waves Method (MASW): Brief Theory and Application to Near Fault Zone Identification - Handoyo, Handoyo (Badan Geologi, 2024)
The characterisation of near subsurface geological features such as sedimentary layer thickness distribution andnear-surface geological structures are interest and continues to be studied to understand the complete conditions in thesubsurface. One geophysical method that can be used for characterising shallow targets is the Multichannel Analysisof Surface Waves (MASW) method. The MASW method is a method that utilises the dispersive nature of surface wavesto model the shear wave velocity distribution in each layer vertically (Vs-depth model). The MASW method consists ofthree stages: acquisition, processing, and inversion. In this paper, we describe the general concept/theory of MASWand its application to characterise a shallow fault zone at a target depth of about 150 m in the active zone, IberianPeninsula, Spain. This study is supported by trenches data as a marker for the fault plane in the study area. Basedon the study and results obtained in this paper, it is hoped that it can provide a brief theory regarding the MASWmethod for the benefit of learning and advancing science and technology in Indonesia. Moreover, it is also hopedthat the application of the MASW method in Indonesia will continue to develop and can be used with wider interests.